Application of pediatric risk of mortality-III score to predict outcome in critically sick children admitted in a tertiary care pediatric unit in a developing country - Das, Krishna Kumar; Kumar, Ajay; Paul, Premila; Aggarwal, K C (Indian Journal of Child Health, 2016)
Objective: The aim of this study is to assess the utilization of the pediatric risk of mortality-(PRISM)-III score to predict mortality in critically sick children and determination of mortality risk factors in a tertiary care pediatric unit. Materials and Methods: In this cross-sectional descriptive study, 100 children admitted during an 18-month period were enrolled in the study. PRISM-III score and mortality risk were calculated. Follow-up was noted as death or survival. Results: Of 100 patients, 27 died and 73 survived. The 47% of the patients were males. The PRISM-III score was 0-9 in 75%, 10-19 in 15% and 20-29 in 8%, ?30 in 2% of patients. PRISM-III score showed an increase of mortality from 8% in 0-9 score patients to 100% in ?20 score. PRISM-III score was significantly associated with study variables such as duration of hospital stay, mental status (Glasgow Coma scale <8), and blood pH <7.28 (p<0001). Conclusion: PRISM-III score showed good predictive value (94.5%) and adequate discriminatory capacity (area under receiver operating characteristics curve 90.8%), and thus constitutes a useful tool for the assessment of prognosis for pediatric patients.